KAJIAN KERAGAAN KARAKTERISTIK DAN TINGKAT PENGETAHUAN PETANI TENTANG SISTEM INTEGRASI SAPI DAN KELAPA SAWIT (SISKA) DI KECAMATAN PANGKALAN LESUNG, KABUPATEN PELALAWAN - Susy Edwina; Evy Maharani (Universitas Sebelas Maret, 2014)
Cattle development through regional integration system of oil palm plantations has a great opportunity to be developed. The idea of integration of beef cattle breeding business can overcome the problem of land scarcity. application of SISKA by Group Maju Bersama in the village of Bukit Harapan Siak has reached the stage of independence, but the number of farmers who have applied SISKA very limited. This is because the success of SISKA not only determined by the technology and the support of natural resources, but also by farmer characteristics. This study aims to determine the internal and external characteristics of farmers who implement systems integration; and the level of their knowledge of SISKA. This study uses a survey to determine Farmers Group Patient nrimo purposive. The qualitative descriptive data analysis using ordinal scale is Likert Scale. The results show the performance of the internal characteristics of farmers by age 90.91 % are in the productive age farmers had high school education or equivalent 63.64 %, with an average tenure of 3 ha, number of dependents on average 4 persons, the average farm experience 18 years, kekosmopolitan including high category seen from the number of resources with a score of 4.18, searching for information with a score of 4.18 and 4.45 the motivation for information. The external characteristics of farmers as a whole are in the category of being seen from the intensity of the extension with a score of 4.12, the accuracy of the channel extension with a score of 3.80, the number of resources of 3.23, the price of the means of production with a score of 3, the availability of low production with a score of 1,86, the environmental carrying capacity score of 3.95. The results of the study indicate the level of their knowledge of SISKA including high category.